Efficient activation of a visible light-activatable CA4 prodrug through intermolecular photo-unclick chemistry in mitochondria - Bio, Moses; Rajaputra, Pallavi; Lim, Irene; Thapa, Pritam; Tienabeso, Bomaonye; Hurst, Robert E.; You, Youngjae (Chemical communications (Cambridge, England), 2017)
Photo-unclick chemistry mediates visible and near IR-controlled drug release via a singlet oxygen (SO)-cleavable linker. Due to the limited diffusion distance of SO in biological systems, a photosensitizer and the SO-cleavable linker have been conjugated in one molecule or mixed in nano-drug delivery systems. In this communication, we demonstrate a new strategy to activate prodrugs with photo-unclick chemistry in an intermolecular fashion using an SO-cleavable CA4 prodrug and a mitochondria-specific photosensitizer, protoporphyrin IX, formed from prodrug hexyl-5-aminolevulinate.